A pilot study of research methods for determining the impact of pictorial cigarette warning labels among smokers - Mays, Darren (BioMed Central, 2014)
BACKGROUND: Science to determine the impact of pictorial cigarette warning labels can inform decisions about warning label implementation and adjustments to their contents to maximize impact. This pilot study builds from earlier research on plain cigarette packaging to examine the feasibility of a method for determining the impact of pictorial warnings among smokers. FINDINGS: The study was a prospective, within-subjects pilot trial where smokers ages 18–30 (n = 10) were exposed to pictorial warnings on their cigarette packs. On day one, participants completed a baseline interview with an expired carbon monoxide reading and affixed pictorial warning labels to their cigarette pack(s) they would use the next day. On day two, participants completed mobile phone text message assessments of smoking behaviors and protocol adherence. On day three, participants completed a follow-up interview similar to baseline. We achieved 100% sample retention and adherence with procedures. Compared with baseline assessments of perceptions and behaviors related to existing text-only warnings, at follow-up participants were more likely to report that pictorial warnings used during the study were noticeable (M 4.1, SD 1.3 vs. M 2.7, SD 1.2, p = .013), stopped them from smoking (M 1.6, SD 0.8 vs. M 1.1, SD 0.3, p = .052), and conveyed health risks of smoking (M 3.5 SD 1.3 vs. M 2.2, SD 1.1, p = .006). At follow-up, participants also reported the protocol was acceptable. CONCLUSIONS: These findings suggest this is a feasible method that with further validation could provide evidence that can inform decisions regarding implementation of pictorial cigarette warnings.